ANALYSIS OF CONCEPT 3A IN TOURISM DEVELOPMENT (CASE STUDY: DUSUN IV, DESA DENAI LAMA, KAB. DELI SERDANG) - Dafa Rizky Prayoga; Afiaty Zata Dini; Lara Anjelita Tarigan; Putri Andiana Sari; Darwin P. Lubis; Sendi Permana (Jurnal Samudra Geografi, 2022)
The research is based on the world of tourism which is developing very rapidly. In the midst of a pandemic and a slowing economy, the Denai Lama Tourism Village is here to be one of the options for a just tourism village, which provides economic movement for the community and opens the widest possible job opportunities, and as much as possible. This study aims to analyze the 3A concept and conclude the SWOT concept in tourism development in Hamlet IV, Denai Lama Village, Kab. Deli Serdang This research uses a qualitative-descriptive approach. The informant in this study was the Head of Hamlet IV, namely Mr. Sucipto. This study uses field observations, interviews, and literature studies. The analytical technique used is the Miles and Herberman interactive analysis model and SWOT analysis. The results found are the existence of Paloh Naga Agrotourism in Hamlet IV, Denai Lama Village, which has become a tourism icon in this area. There are a number of other supporting tourism objects with great potential. However, there are still some obstacles that become obstacles in the development of this tourist area. With the existence of alternative tourism development strategies, it can help the development of this area to be more advanced and fulfill all the things needed.